Shallot-Peel Extract Supplementation Increases Glutathione Levels in Gastritis Rat Model - Zahrah Febianti; Bagas Wahyu Utama; Adelia Handoko (Althea Medical Journal)
Background: Mefenamic acid can cause gastritis. Glutathione is one of the oxidative stress defense mechanisms and nutrient supplementation containing high antioxidants. Peel of shallot (Allium cepa var. Ascalonicum) contains higher antioxidant compounds and may increase glutathione levels. This study aimed to analyze the effect of shallot peel extract supplementation on gastric glutathione (GSH) levels in gastritis rats model.